Characterization and modelling of aerosol droplet in absorption columns. (March 2017) - Majeed, Hammad; Knuutila, Hanna K.; Hillestad, Magne; Svendsen, Hallvard F.
Highlights: Aerosols may lead to amine emissions many times larger than in mist free gas phase. Outlet droplet composition close to bulk liquid regardless of initial values. Droplet grows to more than three times original size. 2D model necessary for fast reacting systems. The Kelvin effect is significant for submicron droplets but not strong. Abstract: Formation of aerosols can cause serious complications in industrial exhaust gas cleaning processes. Small mist droplets and fog formed can normally not be removed in conventional demisting equipment because their submicron size allows the particles or droplets to follow the gas flow (Schaber et al., 2002). As a consequence of this aerosol based emissions in the order of grams per Nm 3 have been identified from PCCC plants (Khakharia et al., 2015 ). In absorption processes aerosols can be created by spontaneous condensation or desublimation processes in supersaturated gas phases or as a result of droplets or particles entering with the exhaust gas. Undesired aerosol formation may lead to amine emissions many times larger than what would be encountered in a mist free gas phase in PCCC development. It is thus of crucial importance to understand the formation and build-up of these aerosols in order to mitigate the problem. This paper presents a rigorous model of aerosol dynamics leading to a system of partial differential equations. In order to understand the changes taking place with a particle entering an absorber an implementation of the model is created in Matlab. The model predicts the development in droplet size, droplet internal variable profiles and the mass transfer fluxes as function of position in the absorber, and thus also at the outlet. The Matlab model is based on a subclass method of weighted residuals for boundary value problems named, the orthogonal collocation method. The model comprises a set of mass transfer equations for transferring components and the necessary diffusion reaction equations to describe the droplet internal profiles for all relevant constituents. Also included is heat transfer across the interface and inside the droplet. This paper presents results describing the basic simulation tool for the characterization of aerosols formed in CO2 absorption columns and gives examples as to how various entering droplets grow or shrink through an absorber and how their composition changes with respect to position.